Association of Plasminogen Activator Inhibitor-1 4G/5G and Angiotensin-Converting Enzyme I/D Polymorphisms with Recurrent Pregnancy Loss in Sudanese Women: A Case-Control study - Hanan K. Ahmed; Amanda G. Elgoraish; Selma Elmalieh Abdalla; Asaad MA. Babker; Ayman Hussien Alfeel; Amin Omer Ibrahim Abbas; Khalid Abdelsamea Mohamedahmed; Salaheldein G Elzaki (International Journal of Biomedicine, 2023)
The aim of our study was to investigate the relationship between the ACE I/D and PAI-1 4G/5G polymorphisms and RPL in Sudanese women. Methods and Results: A total of 232 people participated in this case-control study, including 119 women who had been diagnosed with RPL (Case group) and 113 healthy women (Control group). The case group (RPL) consisted of Sudanese women (mean age of 31.3+5.9 years) who had at least three unfavorable pregnancy outcomes. Women in the control group (Control) were matched by age (mean age of 30.3+5.4 years), had at least two healthy pregnancies, and had no history of unfavorable pregnancy outcomes or recurrent losses. Genomic DNA samples were isolated from the whole blood by using the GF-1 Blood DNA Extraction Kit (Vivantis Technologies Sdn. Bhd., Malaysia) according to the manufacturer`s protocol. The status of the PAI-1 4G/5G and ACE I/D polymorphism was determined by PCR. Analysis of the multiplicative and additive models for the ACE I/D polymorphism showed a significant risk of RPL with the carriage of the D allele (OR=2.07, 95% CI: 1.28-3.35, P=0.003) and the homozygous DD genotype (OR=2.40, 95% CI: 1.34-4.29, P=0.008). The multiplicative and additive models for the PAI-1 4G/5G polymorphism showed a significant risk of RPL with the carriage of the 4G allele (OR=3.11, 95% CI: 2.12-4.58, P=0.000) and the homozygous 4G/4G genotype (OR=3.09, 95% CI: 1.77-5.39, P=0.000). However, the carriage of risk-polymorphic markers, the ACE I/D and PAI-1 4G/5G polymorphisms, was not associated with the number of RPL. The combined carriage of the homozygous DD genotype and heterozygous ID genotype of the ACE I/D polymorphism with the homozygous 4G/4G genotype of the PAI-1 4G/5G polymorphism occurs significantly more often in RPL women than healthy women (P=0.000 and P=0.006, respectively). Carriage of the PAI-1 5G/5G genotype in healthy women was not associated with the ACE I/D polymorphism. Conclusion: Testing for the ACE I/D and PAI-1 4G/5G polymorphisms should be part of the standard examination for patients with RPL.